Relevant aspects of digitalization of land legal relations - Ibraev А.С. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2021)
The article considers the foreign experience of using information and digital tools in land legal relations. Considering the current legislation and state programs for the digitalization of the economy, the article presents specific recommendations for the use of digital technologies in land relations. In particular, the use of blockchain, bitcoin, and big data technologies, will minimize bureaucracy and corruption risks. Considering the current threats (hacker attacks) and the timing of the provision of public services, it is proposed to use blockchain technology for the rapid and secure provision of land to private ownership or the granting of temporary land use rights. The integration of digital tools into public relations will allow optimizing the speed and quality of public services. Land relations in the Republic of Kazakhstan should be automated and digitized to eliminate possible risks and disputes between subjects of land legal relations, including the state.